समकालीन कला, साहित्य, संगीत एवं नृत्य का विज्ञान एवं समाज विज्ञान से अंतर्संबंध - Bharadwaj, Kumkum; Porwal, Tina; I. U. Khan; Charri, Sudhir Kumar; Rani, Poonam; Rani, Versha (International Journal of Research -GRANTHAALAYAH, 2026)
Dear Readers and Contributors, Greetings from the Department of Fine Arts, Maharani Laxmibai Government Girls Postgraduate College, Indore (Madhya Pradesh). The Department of Fine Arts is organizing an International Research Seminar on the theme: “समकालीन कला, साहित्य, संगीत एवं नृत्य का विज्ञान एवं समाज विज्ञान से अंतर्संबंध” (Contemporary Art, Fine Arts, Literature, Music and Dance: Interrelationship with Science and Social Sciences) to be held on 16–17 January 2026. On this significant academic occasion, selected research papers presented in the seminar will be considered for publication in a Special Issue, in collaboration with our Publication Partner – Granthaalayah Publications and Printers. The seminar aims to explore the diverse dimensions of Indian art, culture, and literature, and to encourage interdisciplinary dialogue between arts, science, and social sciences. It seeks to promote research, innovation, creativity, preservation of cultural heritage, and holistic academic development. Scholars are invited to contribute original and unpublished research papers related to the broad thematic areas, including contemporary art and society, history and traditions of Indian art, folk and tribal arts, social consciousness in art and literature, global perspectives of art and culture, the interrelationship of art and modern technology, and Indian knowledge traditions with innovation. We sincerely invite you to participate in this international academic initiative and contribute your valuable research to the Special Issue. Your scholarly contribution will enrich the discourse and strengthen research in traditional as well as contemporary artistic domains. Issue Editor: Dr. Kumkum Bharadwaj Professor (HOD) in Fine Arts, Government Maharani Laxmi Bai Girls Postgraduate College, Indore, India Email: drkumkum.bharadwaj@mp.gov.in / kumkumbh@hotmail.com Dr. Tina Porwal PhD, Government Maharani Laxmi Bai Girls Postgraduate College, Indore, India Email: tina.porwal@shodhkosh.com / sethiya.tina@gmail.com Dr. I. U. Khan Professor, Drawing and Painting, Rajasthan University, Jaipur, India Dr. Sudhir Kumar Charri Assistant Professor, Drawing and Painting, Maharani Laxmi Bai Government Girls PG College, Indore, India Dr. Poonam Rani HOD Fine Arts, Mangalayatan University, Beswan, Aligarh, UP, India Dr. Versha Rani Assistant Professor, Department of Drawing & Painting, H.V.M. P.G. College, Raisi, Haridwar, Uttarakhand, Sri dev Suman Uttarakhand Vishwavidyalaya, Badshahithol, New Tehri, Garhwal, Uttarakhand, India